Sustainable Literacy of Climate Change: A Survey Study on Pre-Service Elementary Teachers' - Fatimah, Siti; Rahayuningsih, Margareta; Marianti, Aditya (International Journal of Basic Educational Research, 2024)
Sustainability literacy is a crucial skill that should be introduced to students as a way to achieve sustainable development. Environmental issues are one of the main goals in sustainable development. The objective of this study is to analyze the sustainability literacy profile of pre-service elementary teachers related to climate change. This research is a survey study. The subjects of this study are 156 pre-service elementary teachers. Data collection techniques used semi-open questionnaires. Data analysis techniques used descriptive techniques. The results of the analysis show that the sustainability literacy of the students falls into the very good category, with an average score of 84.85%. The Sustainable Knowledge (SK) dimension is the highest compared to the other dimensions, with a percentage of 92.96%. Meanwhile, the Sustainable Behaviour (SB) dimension is the lowest, with a percentage of 76.75%.